1990
DOI: 10.1192/bjp.157.5.748
|View full text |Cite
|
Sign up to set email alerts
|

Acute Blocking of Naloxone-Precipitated Opiate Withdrawal Symptoms by Methohexitone

Abstract: In a double-blind placebo-controlled trial of 18 patients, methohexitone blocked objective signs of opiate withdrawal caused by a bolus injection of naloxone. Furthermore, in continuing the naloxone therapy for 48 hours, no withdrawal signs appeared. Levels of withdrawal distress returned to normal levels within six days. This approach can be regarded as an effective and well tolerated withdrawal therapy with low drop-out rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…* An early doubleblind study 42 described methohexitone anesthesia in 18 individuals randomly assigned to receive naloxone or placebo. But the study only compared withdrawal induced by naloxone vs placebo and included only a week of followup.…”
mentioning
confidence: 99%
“…* An early doubleblind study 42 described methohexitone anesthesia in 18 individuals randomly assigned to receive naloxone or placebo. But the study only compared withdrawal induced by naloxone vs placebo and included only a week of followup.…”
mentioning
confidence: 99%
“…19,32 Despite mixed results, the current research ¢ndings demonstrate that patients found naloxone-assisted detoxi¢cation acceptable and tolerable using a method that requires minimal diazepam sedation. This provides further support for the assertion by Buntwal et al 14 that there may be a ''middle way'' of increasing the rapidity of opiate detoxi¢cation without incurring the risks associated with general anaesthesia.…”
Section: Discussionmentioning
confidence: 82%
“…Early studies demonstrated that this transition could be made rapidly by inducing the withdrawal under general anesthesia with high-dose antagonists. 7,8 Furthermore, data from early studies suggested that when high-dose opioid antagonists induced withdrawal, symptoms were greatest within the first few hours of treatment and declined to tolerable levels rapidly.…”
Section: Discussionmentioning
confidence: 99%